Retroperitoneal lymphadenopathy: an extrahepatic feature of chronic active hepatitis. Issue 823 (May 1994) - Hayek, T.; Markel, A.; Goldfeld, M.; Ben-Arie, Y.; Brook, G. J.
Abstract : We report a patient with chronic active hepatitis in whom one of the initial findings was retroperitoneal lymphadenopathy, detected by abdominal ultrasound examination. Extrahepatic presenting findings of chronic active hepatitis may include arthritis, urticaria, pleurisy and pericarditis, while abdominal lymphadenopathy has been only rarely described. Chronic active hepatitis should be included in the differential diagnosis of abdominal lymphadenopathy.